Pembiayaan Murabahah Dan Ijarah Terhadap Tingkat Kesehatan Bank Pada Bank Umum Syariah - Meris Terawati (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
This study’s aimis to determine the effect of murabahah financing and ijarah financing on the bank soundness of sharia banks in the annual financial statements of islamic banks. Independent variables studied were murabahah studied are murabahah (X1), ijarah (X2),while the dependent variable in this study was bank soundness (Y). This study uses 30 data from the annual financial statements of 6 bank sharia banks in the period 2012-2016. Data processing using logistic regression with SPSS 23.0. Partially, the result of the test shows that murabahah and ijarah financing have a significant effect on bank soundness. The simultaneous test showed that all independent variables in this study had a significant influence on bank soundness.